2020
DOI: 10.1055/s-0040-1721067
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Comparison of Serum and Transcutaneous Bilirubin in Indian Neonates

Abstract: The objective of this study was to compare the transcutaneous bilirubin (TcB) with total serum bilirubin (TSB) and to find out the effect of phototherapy on correlation of TcB and TSB during and after phototherapy in Indian neonates. Prospective observational study was performed at neonatal intensive care unit of Uttar Pradesh University of Medical Sciences, Saifai, Etawah, India. Blood samples for TSB estimation of 276 jaundiced neonates were sent, and simultaneously, TcB was measured at forehead and sternum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 32 publications
0
6
0
5
Order By: Relevance
“…Transcutaneous bilirubin assessments are routinely used in many Western Countries and in hospital settings of some tropical countries. Their reliability in populations with more pigmented skin has not been tested widely (19-21) and was evaluated against capillary TSB levels in neonates of Karen and Burman ethnicity here for the first time. Results from this study indicate that TcB values, with an appropriate simple correction, can be used reliably against TSB nomograms to identify neonates who need confirmatory laboratory blood tests to detect clinically significant bilirubin levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcutaneous bilirubin assessments are routinely used in many Western Countries and in hospital settings of some tropical countries. Their reliability in populations with more pigmented skin has not been tested widely (19-21) and was evaluated against capillary TSB levels in neonates of Karen and Burman ethnicity here for the first time. Results from this study indicate that TcB values, with an appropriate simple correction, can be used reliably against TSB nomograms to identify neonates who need confirmatory laboratory blood tests to detect clinically significant bilirubin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Transcutaneous bilirubin assessments are routinely used in many Western Countries and in hospital settings of some tropical countries. Their reliability in populations with more pigmented skin has not been tested widely (19)(20)(21) represents an initial insurmountable investment for most constrained-resource settings, but other transcutaneous devices might be as accurate and more affordable (24). Other cheaper screening tools have been tested, such as icterometers (25,26) and phone-based apps (27)(28)(29), and when properly evaluated could be used by health workers at birthing centers and in remote settings, and even by parents (30) after discharge from the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…There have been concerns about the reliability of TcB among darkly pigmented infants based on how the bilirubinometer uses a light source (xenon) to compute for wavelength differences between skin and subcutaneous tissue ( 27 ). However, recent studies have shown TcB readings are not affected by skin color ( 28 ). High correlation between TcB and TsB has also been shown among infants of Asian descent such as Japanese ( 29 ), Chinese ( 24 ), Mongolian ( 30 ) and specifically those of Malay descent (darker skin)—Indonesian ( 31 ), Myanmar ( 12 ) and Thai ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers and healthcare professionals should be aware of the potential impact of ambient light and take measures to standardize the measurement conditions to obtain reliable TcB readings. Effect of TSB Level: TcB measurements tend to be less accurate and may underestimate TSB levels at higher concentrations ( 203 ). Consequently, as TSB levels increase, the rate of false-negative TcB results may rise.…”
Section: Non-invasive Approaches For Jaundice Screening and Their Lim...mentioning
confidence: 99%
“…Nevertheless, when employing suitable cutoff values, TcB measurements remain effective as a screening tool, even when TSB levels exceed 15 mg/dl. Effect of Phototherapy on TcB Measurements: The use of phototherapy can lighten an infant's skin, potentially compromising the reliability of visual assessments of jaundice and TcB measurements ( 181 , 203 ). However, if specific areas of the skin remain shielded during phototherapy, TcB measurements from those areas can be employed to monitor treatment response.…”
Section: Non-invasive Approaches For Jaundice Screening and Their Lim...mentioning
confidence: 99%